2004
DOI: 10.1002/ijc.20023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serum deprivation on constitutive production of granulocyte‐colony stimulating factor and granulocyte macrophage‐colony stimulating factor in lung cancer cells

Abstract: We previously established 2 lung cancer cell lines, OKa‐C‐1 and MI‐4, which constitutively produce an abundant dose of granulocyte‐colony stimulating factor (G‐CSF) and granulocyte macrophage‐colony stimulating factor (GM‐CSF). Many other cases with G‐CSF or GM‐CSF producing tumors have been reported up to the present. However, the biological properties of the overproduction of G‐CSF and GM‐CSF by tumor cells have not been well known. Several reports demonstrated the presence of an autocrine growth loop for G‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…(36,37) CSF extend the life span of mature leukocytes by inhibiting their apoptotic death; this function may not be confined only to hematopoietic cells, but may extend also to cancer cells. (38,39) In the present study, it was observed that almost all lung cancer cell lines produced various kinds of cytokines. These cytokines seemed to have such functions as tumor progression, angiogenesis and an inhibition of the immune response.…”
Section: P-valuementioning
confidence: 52%
“…(36,37) CSF extend the life span of mature leukocytes by inhibiting their apoptotic death; this function may not be confined only to hematopoietic cells, but may extend also to cancer cells. (38,39) In the present study, it was observed that almost all lung cancer cell lines produced various kinds of cytokines. These cytokines seemed to have such functions as tumor progression, angiogenesis and an inhibition of the immune response.…”
Section: P-valuementioning
confidence: 52%
“…Mroczko et al demonstrated that CSFs could be useful in diagnostics and monitoring of NSCLC (5). Some studies show that CSFs produced by lung cancer cells might promote tumor progression through an autocrine mechanism (6,7). Exogenous CSFs also promote invasion by lung cancer cells through the enhanced production of extracellular matrixdegrading proteinases by the tumor cells or prolong tumor cell survival (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated a MAPK-and NF-Bmediated autocrine growth loop for G-CSF in nonhematopoietic tumor cells in which serum deprivation stimulated constitutive production of G-CSF (21,36). Although known for some time to be proliferative for granulocytes and human endothelial cells (5,26), there is only one other report in the literature describing expression of G-CSF in human VSMC (34).…”
Section: Discussionmentioning
confidence: 96%